Review of the All-Russian Scientific Conference “Tendencies of Development of Law in Sociocultural Space: Zhidkov Readings - 2017” (Moscow, 24-25 March, 2017) - Nemytina, M.V.; Mikheeva, T.T.; Sorokina, E.A. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ I͡U︡ridicheskie nauki, 2017)
On 24-25th of March 2017 the All-Russian Scientific-Practical Conference “Tendencies of development of law in sociocultural space: Zhidkov readings - 2017” took place in People’s Friendship University of Russia (RUDN University). The conference is traditionally devoted to the memory of the famous scientist, Professor O.A. Zhidkov. It was co-organized by Institute of State and Law of the of the Russian Academy of Sciences (RAS), Herzen State Pedagogical University of Russia , Association of Law Schools of Russia. The conference featured the plenary meeting, four panel sessions, two round tables and school of young scientists. During the conference different aspects of legal issues were discussed, including its methodological, theoretical and application nature. In their reports, the participants, inter alia, devoted attention to discussion trends of the development of law and legal science from the perspective of historical development, the current and future prospects. Present review includes general conception of the conference, participants’ main ideas and fragments of their speeches mirrored to certain extent the level of comprehending the conference’ main problem by scientific society.